When It Hurts the Most: Timing of Parental Job Loss and a Child's Education - Paul Bingley; Lorenzo Cappellari; Marco Ovidi (Institute of Labor Economics (IZA), 2023)
We investigate the stages of childhood at which parental job loss is most consequential for their child's education. Using Danish administrative data linking parents experiencing plant closures to their children, we compare end-of-school outcomes to matched peers and to closures hitting after school completion age. Parental job loss disproportionally reduces test taking, scores, and high school enrolment among children exposed during infancy (age 0-1). Effects are largest for low-income families and low-achieving children. The causal chain from job loss to education likely works through reduced family income. Maternal time investment partially offsets the effect of reduced income.
Keywords: J13; D10; I24; 330; parental labor market shocks; intergenerational mobility; child development